The effect of injection mold gate construction on selected properties of polyethylene moldings - Bociąga, E. (Polimery, 2022)
Results of property measurements of test specimens are considerably affected by the method and by conditions under which the materials is injected into the mold. Mold design is of particular importance. The molded piece produced is reliable only when the mold is filled with a material introduced in the laminar flow mode.